GLASS WASTE POWDER UTILIZATION IN HIGH PERFORMANCE CONCRETE - Diana Mariaková; Tomáš Vlach; Tereza Pavlů (Acta Polytechnica CTU Proceedings, 2019)
This paper deals with investigation of high-performance concrete (HPC) with full replacement of the silica powder by the waste glass powder. The silica powder was replaced by two types of the waste glass powder, originated from different sources (waste glass powder from grinding jewelry and milling of municipal waste glass). The properties of the waste glass powder were examined and compared with the silica powder. The mechanical and durability properties of three HPC mixtures were experimentally verified. The bulk density, flexural strength, and compressive strength were tested on beams 40 × 40 × 160mm at age 28 and 60 days and after 0, 25, 50, 75 and 100 freeze-thaw cycles. There were observed slightly worse properties of mixtures with the waste glass powder in comparison with reference HPC.